The Role of Cytochrome c on Apoptosis Induced by Anagrapha falcifera Multiple Nuclear Polyhedrosis Virus in Insect Spodoptera litura Cells - Liu, Kaiyu (Public Library of Science, 2012)
There are conflicting reports on the role of cytochrome c during insect apoptosis. Our previous studies have showed that cytochrome c released from the mitochondria was an early event by western blot analysis and caspase-3 activation was closely related to cytochrome c release during apoptosis induced by baculovirus in Spodoptera litura cells (Sl-1 cell line). In the present study, alteration in mitochondrial morphology was observed by transmission electron microscopy, and cytochrome c release from mitochondria in apoptotic Sl-1 cells induced with Anagrapha falcifera multiple nuclear polyhedrosis virus (AfMNPV) has further been confirmed by immunofluoresence staining protocol, suggesting that structural disruption of mitochondria and the release of cytochrome c are important events during Lepidoptera insect cell apoptosis. We also used Sl-1 cell-free extract system and the technique of RNA interference to further investigate the role of cytochrome c in apoptotic Sl-1 cells induced by AfMNPV. Caspase-3 activity in cell- free extracts supplemented with exogenous cytochrome c was determined and showed an increase with the extension of incubation time. DsRNA-mediated silencing of cytochrome c resulted in the inhibition of apoptosis and protected the cells from AfMNPV-induced cell death. Silencing of expression of cytochrome c had a remarkable effect on pro-caspase-3 and pro-caspase-9 activation and resulted in the reduction of caspase-3 and caspase-9 activity in Sl-1 cells undergoing apoptosis. Caspase-9 inhibitor could inhibit activation of pro-caspase-3, and the inhibition of the function of Apaf-1 with FSBA blocked apoptosis, hinting that Apaf-1 could be involved in Sl-1 cell apoptosis induced by AfMNPV. Taken together, these results strongly demonstrate that cytochrome c plays an important role in apoptotic signaling pathways in Lepidopteran insect cells.